Book review: Tamizhini, In the Shadow of a Sword: The Memoir of a Woman Leader in the LTTE. (June 2023) - Geetha, V.
Tamizhini, In the Shadow of a Sword: The Memoir of a Woman Leader in the LTTE (Yoda Press, 2021), 197 pp., ₹495, ISBN 9789353886837 (Paperback).